Safawidzkie adaptacje chińskich talerzy typu kraak - Macioszek, Amelia (Studia Azjatystyczne, 2015)
Decorative motives known from the Chinese blue-and-white porcelain began to appear massively on Persian ceramics between the 14th and 17th century. Interestingly, the initial role of adaptations being a  substitute for an expensive original became something more – a source of inspiration for making new vessels decorated not only in cobalt blue but also in colorful slips. The article is dedicated to an analysis of Persian adaptations of Chinese kraak porcelain made during the Safavid period (1501-1732). Due to the fact that the process of adaptation was very complex and there is no 1:1 copy of a kraak dish in Iran, author in her research has to focus on comparing individual motifs instead of the whole vessels. She introduces new categorization of the adapted designs and divides them into 4 groups depending on how close they resemble the Chinese origi nals: in group 1 called literal adaptations the motifs are most similar to the originals; in group 2 named edited adaptations are those that have an element added or taken away; in group 3, altered adaptations, the designs undergo changes in style but still bear the basic characteristics of the originals; in group 4, free adaptations, are those that only resemble the Chinese ones.